What World Is Knocking? Responding to a World in Crisis with Polyphonic Storying - Angela Molloy Murphy (Australian Journal of Environmental Education)
The case has been made — many of the approaches humans employ to address environmental collapse are founded on the very (White, Western, colonial, positivist, capitalist, human supremacist) thinking that advanced planetary degradation in the first place. We know how this story ends. If we continue perpetuating narratives of management, mastery and (White) human supremacy through environmental education (EE) and confront environmental issues accordingly, we will only advance Earth’s demise. Only by countering narratives of human exceptionalism and acknowledging the entangled and deeply relational nature of our existence can we begin to envision worlds of care for all. Reconceptualising EE as a polyphonic storying of relations with the more-than-human “keeps the way open” for humans to reassess our role in the world.